A comparative study on Maternal Fetal Attachment behaviors of women with and without history of perinatal loss - Mehran, Pegah; Simbar, Masumeh; Shams, Jamal; Nasiri, Navideh (Advances in Nursing & Midwifery, 2013)
Abstract Background: Maternal mental health and motherhood adaption behaviors during pregnancy have been paid much attention during recent years. This study aims to compare maternal fetal attachment behaviors of women with and without history of perinatal loss Material and Methods: This was a comparative study on women in two groups of women with and without history of perinatal loss. The participants were recruited using a convenience method of sampling, from prenatal care services affiliated to Shahid Behesti University of Medical Sciences. Tools for data collection included a questionnaire with demographic- and fertility- related questions as well as the Persian version of Cranly’s MFA questionnaire The MFAS scale included questions in groups including role-taking, differentiation of self from fetus, interaction with fetus, attribution of characteristics to fetus, and giving of self. Data was analyzed by SPSS and using t, ANOVA, regression, Chi square, Pearson correlation and Mann Whitney tests. Results: One hundred women aged years (Mean±SD), with weaks gestational age participated in the study. Finding showed that total mean score for MFA of women with history perinatal loss ( Percent) is not significantly different from the mean score of primigravid women without such a history ( Percent) (p< ). Primigravid women without history of perinatal loss had a significantly higher score for the behaviors related to “differentiation of self from fetus” comparing to women with history of perinatal loss But, two groups were not different regarding to other groups of MFA behaviors (p< ). Conclusion: Maternal-fetal attachment behaviors of women with and without history of perinatal loss were not different. However women with the history of perinatal loss shows lower scores for behaviors related to differentiation of self from fetus. Key word: Pregnancy, perinatal loss, Maternal Fetal Attachment